Critical Synthesis Package: Cultural Competence OSCE (ccOSCE) - Anna T. Cianciolo (Association of American Medical Colleges, 2013)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health sciences education for the Cultural Competence OSCE (ccOSCE), and (2) a copy of the ccOSCE instrument and checklist developed by Alexander Green, MD. The ccOSCE is a one-station, performance-based assessment of medical students' ability to elicit and comprehend the sociocultural causes of health outcomes. It features a middle-aged ethnic minority woman for whom a combination of sociocultural factors, including an inaccurate understanding of hypertension, have led to medication non-adherence and complaints of inability to control her blood pressure. Within a 15-minute time limit, examinees must take a patient history, present the patient's case orally to an examiner, and complete a short-answer question about the case. Performance is rated using multiple, conceptually founded checklists. The ccOSCE may augment an OSCE that does not assess cultural competence, but its fit to other OSCE stations will require negotiation of implementation procedures and assessment criteria as well as quantitative evaluation to ensure the reliability of the full exam. The ccOSCE does not contain instructions for how to score each checklist or how checklist scores should be aggregated to produce a summary score. Such guidance is necessary to evaluate the psychometric properties of the measure (e.g., difficulty, score distributions, part-whole correlation with OSCE total score, inter-rater reliability, etc.) as well as other validity evidence (e.g., fairness of scoring procedures, relation to other measures of cultural competence and communication skills, sensitivity to instruction in these areas, etc.). However, use of the ccOSCE may raise awareness of how to assess cultural competence via modifications to extant OSCE stations.